Timescales of the Climate Record in the South Polar Ice Cap of Mars - Becerra, Patricio; Sori, Michael M.; Thomas, Nicolas; Pommerol, Antoine; Simioni, Emanuele; Sutton, Sarah S.; Tulyakov, Stepan; Cremonese, Gabriele (Geophysical Research Letters, 2019)
The South Polar Layered Deposits (SPLD) are the largest water ice reservoirs on Mars. Their accumulation is believed to result from climate oscillations that drive the movement of ice and dust on the surface. The High-Resolution Imaging Science Experiment and the Colour and Stereo Surface Imaging System have imaged exposures of its internal structure in troughs and marginal scarps. Here we use the stereo imaging products of these instruments to extract stratigraphic profiles representative of various locations throughout the SPLD. Through wavelet and series-matching analyses of these profiles, we reveal periodicities in the stratigraphy that correlate to the orbital oscillations that drive climate change on Mars and that have been observed to force the accumulation of the north polar cap. We infer that the water ice and dust of the SPLD were deposited at variable rates of 0.13-0.39 mm/year, taking a minimum of 10-30 Myr to accumulate. Plain Language Summary The single location on Mars with the most water ice is in the southern polar ice cap, in the so-called South Polar Layered Deposits (SPLD). Changes in Martian climate through time affect the locations on Mars where ice is stable, and it is believed that these changes drove the accumulation of layers upon layers of ice and dust in the SPLD. The High-Resolution Imaging Science Experiment and the Colour and Stereo Surface Imaging System are satellite cameras that have photographed troughs and scarps within the SPLD to produce 3-D views of this layered internal structure. We analyzed this structure and found patterns in the layering related to variations of Mars' orbit and spin axis. These variations drive climate change on Mars, so our analysis confirms the connection between the SPLD and Mars' astronomical parameters. From this relationship, we inferred that the ice and dust of the SPLD took at least 10-30 Myr to accumulate.